A comparative study between figure of eight suturing technique and omentopexy in closure of peptic ulcer perforation: a prospective study on 60 patients with APACHE II score ≤10 - Bhandari, Vimal; Gunasekaran, Gopalakrishnan; Naik, Debasis; Paruthy, Shivani B.; Choudhry, Lokendra; Garg, Praveen (International Surgery Journal, 2016)
Background:Figure of 8 techniques has been described in the literature for peptic ulcer perforation repair especially when the patient comes late, when the edges of the ulcer and the wall of duodenum are very friable. Methods: Sixty patients included in the study were divided into two groups after randomization. Study group, patients underwent figure of eight suturing technique and Control group, patients underwent Grahm’s technique of omentopexy for peptic ulcer perforation. Results: Only 1 patient from control group developed post-operative bile leak in this study, 3 (10%) patients from study group and 4 (13.33%) patients from control group developed septicaemia, 1 from study group and 2 from control group developed intra-abdominal abscess, 8 (26.66%) in study group and 9 (30%) in the control group developed wound infections, 4 (13.33%) in study group and 7 (23.33%) in the control group developed burst abdomen, 5 (16.66%) from study group and 6 (20%) from control group developed lung complications. Conclusions:The present study is non-inferior than omentopexy in terms of post-operative complications. It can be used as a safe alternative to omentopexy especially when the patient comes late.